Analysis of the evolution pattern and causes of downstream gigantic hydraulic projects. Issue 4 (28th February 2022) - Liu, Linshuang; Luo, Wenguang; Zhang, Liguo; Ming, Bo; Li, Ming; Jiang, Jing
Abstract: The Jingjiang reach, located in the middle Yangtze River, downstream of the Three Gorges Reservoir (TGR), is a typical curved reach. After TGR impoundment, the evolution behaviors of the Jingjiang reach changed, mainly because one or more original factors, including geological conditions, existing projects, bending radius, upper reaches' regimes, and incoming water and sediment changed. In this paper, these influencing factors were investigated by using the measured data and the mathematical models that were proposed by the authors in a previous paper, and consequently, the evolution laws of the curved reach were analyzed. The results showed that the existing river nodes reduced the influence of the upstream river regime on the evolution of curve reaches and also slowed the speed of convex bank scouring and concave bank depositing. Constructed projects could reduce sediment transport intensity from the concave bank to the convex bank. The decrease in incoming sediment after TGR impoundment was beneficial to convex bank scouring. The increase in median water period duration was favorable for convex bank scouring and concave bank depositing. Both convex bank and concave bank were scoured when the incoming sediment concentration decreased sharply. The sediment concentration of suspended load would stabilize near the saturation point, and the riverbed would be scoured when there is sediment concentration under the saturation point, while the riverbed would be deposited when the sediment concentration reaches the saturation point. HIGHLIGHTS: Systematic analysis of channel changes downstream of the Three Gorges Reservoir. The mechanism of upstream water flow change is introduced to analyze the downstream channel change. Considering the impact of human activities on the giant reservoir. Targeted analysis of longer river sections. The results obtained from the study are useful for the management of water resources.